Medicinal use of the unique plant Tinospora Cordifolia: evidence from the traditional medicine and recent research - Khan, Md Moniruzzaman; Haque, M Sadul; Chowdhury, Md Saiful Islam (Asian Journal of Medical and Biological Research, 2017)
Tinospora cordifolia is commonly known as Gulancha in Bangladesh is belongs to Menispermaceae family and it is also available all over the world. It is widely used as a unique ingredient of various natural medicine and traditionally use for numerous aliment like fever, vomiting, diabetes, jaundice, anaemia, polyuria and skin diseases etc. It has hypoglycemic, antipyretic, anti-allergic, Antineoplastic, anti inflammatory, antioxidant, and immuno modulatory properties. A variety of constituents have been isolated from different parts of Tinospora cordifolia, mainly contains alkaloids like Aporphine alkaloids, clerodane diterpenes, berberine, palmatine, tembertarine, tinosporin, magniflorine, choline, Berberine, Palmatine, Tembetarine, Magnoflorine Choline, Tinosporin etc. and Glycoside like Tinocordiside, Tinocordifolioside, steroids, essential oils, mixture of fatty acids and polysaccharides are found in Gulancha plant. This review presents a detailed survey of the literature on traditional and modern knowledge of Tinospora cordifolia for health benefit. Asian J. Med. Biol. Res. December 2016, 2(4): 508-512